Transformation of Religious Moderation through the Deepening of Kitab al-Jawahir al-Kalamiyah in the Women's Pesantren - Arifuddin, Arifuddin; Syahruddin, Syahruddin; Ilham, M.; Karim, Abdul Rahim; Hasanuddin, Muhammad Irfan (Eduprof : Islamic Education Journal, 2025)
Religious moderation is often a fragile concept and limited to ethical recommendations or fiqh rules without touching on the fundamentals of belief. This study does not merely affirm that santriwati in women's pesantren are moderate, but also uncovers the underlying mechanisms of how moderation is produced, namely through mastery of theological foundations that give them the intellectual authority to reconstruct religious discourse from within. A qualitative approach with a case study research type, as well as data collection techniques through observation, interviews, and documentation review were used in this study. Data analysis and testing were also conducted. The results show that the deepening of the kitab al-Jawahir al-Kalamiyah at the women's pesantren Datok Sulaiman Palopo goes beyond mere knowledge transfer to become a complex mechanism for intellectual-spiritual empowerment. The santriwati actively negotiated and reconstructed the meaning of religious moderation, transforming it from a normative concept into a critical ideology rooted in their local context. This transformation was supported by the conducive structural foundation of the pesantren, where its vision, mission, and leadership provided significant space for women agents to operate. The pedagogical foundation for this success lies in the key elements of kitab al-Jawahir al-Kalamiyah. The teaching of tanzih (divine transcendence) instills intellectual humility by emphasizing the absolute difference between the Creator and creation. The concept of hikmah (divine wisdom) is articulated as a theological affirmation of diversity. Furthermore, the text's rational-dialogical question-and-answer method is maximized to train critical thinking and constructive dialogue skills, fostering a deep-seated respect for diversity.